2022
DOI: 10.1101/2022.03.30.486431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longer metaphase and fewer chromosome segregation errors in modern human than Neandertal brain development

Abstract: Since the ancestors of modern humans separated from those of Neandertals, around one hundred amino acid substitutions spread to essentially all modern humans. The biological significance of these changes is largely unknown. Here, we examine all six such amino acid substitutions in the three proteins known to have key roles in kinetochore function and chromosome segregation and to be highly expressed in the stem cells of the developing neocortex. When we introduce these modern human-specific substitutions in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…We refer readers to Mora-Bermúdez et al, 2022 who show an effect of the missense changes in KIF18A and KNL1 on the prolongation of metaphase.…”
Section: Discussionmentioning
confidence: 99%
“…We refer readers to Mora-Bermúdez et al, 2022 who show an effect of the missense changes in KIF18A and KNL1 on the prolongation of metaphase.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of human APs undergoing expansion, a minimization of chromosome segregation errors due to metaphase prolongation would have consequences for the entire progeny of APs, that is, BPs as well as cortical neurons and glial cells. Recent data has brought strong support to these concepts ( Mora-Bermúdez et al, 2022 ).…”
Section: Temporal Differences In Neocortical Stem and Progenitor Cell...mentioning
confidence: 93%
“…Also, the six amino acid variants found in Neandertals are identical to those found in chimpanzees and other non-human great apes. Recent data has shown that the functions of these coding differences between modern and archaic humans are related to the metaphase prolongation observed in modern human vs. chimpanzee and orang-utan organoid APs ( Mora-Bermúdez et al, 2016a , 2022 ).…”
Section: Evolutionary Aspects—are There Differences In Key Players Of...mentioning
confidence: 99%
“…These organoids exhibited changes in organoid morphology and neuronal activity ( Trujillo et al, 2021 ). Recently, Mora-Bermudez and others introduced specific ancestral variants involved in mitotic spindle and kinetochore function in organoids and showed shorter metaphase of apical progenitors compared to the longer metaphase of non-mutated modern human organoids ( Mora-Bermúdez et al, 2022 ). It is interesting to speculate that such evolutionary differences between modern humans and ancestral human species might also be linked to bRG development and function.…”
Section: What Have Organoids Told Us About Brg?mentioning
confidence: 99%